Komizm we wczesnej prozie Antoniego Czechowa (na podstawie opowiadania-scenki pt. "Radość") = Comicality in Anton Chekhov`s early prose (based on a short scene-story entitled "Joy") - Zotova, Nataliia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The sketch essence concerns mechanisms of humour evoked in a short scene-story-entitled "Joy" by Anton Chekhov. The study reconstructs the represented world, including the protagonist`s portrait, plot, action, and composition of the work, as well as its genology. In the text in question, characteristic types of comicality (situational comedy, linguistic comedy, character comedy) and traditional means of comic effects evoking were distinguished, like contrast and perversity of events or opinions; the characters` emotional state modification; exaggeration or over-expression; furthermore, ridiculous anthroponyms and toponyms; stylistic means within lexis and syntax used by the author.
Keywords: Czechow, Anton (1860-1904); filozofia humoru; kategoria estetyczna humoru; komizm; philosophy of humour; aesthetic category of humour; comicality